Type I Kounis syndrome developing following administration of a plasma substitute (a clinical case) - E. V. Kozhevnikova; K. G. Pereverzeva; A. A. Gurbanova; S. S. Yakushin (Рациональная фармакотерапия в кардиологии)
Given the high prevalence of allergic and cardiovascular diseases, clinicians must remain vigilant to the possibility of Kounis syndrome (KS), which involves the cooccurrence of an allergic reaction and acute myocardial infarction (AMI). The article describes a case of KS in a 62-year-old patient, without atherosclerotic coronary artery disease, during the infusion of a plasma-substitute, dextran, used by the patient for self-medication and resulting anaphylactic shock. The diagnosis of AMI was confirmed by elevated myocardial necrosis biomarkers, as well as electrocardiographic and echocardiographic changes. Patient management adhered to current clinical guidelines for AMI and allergic reactions. The distinctive feature of this clinical case is the development of type I KS triggered by dextran, and the multifactorial etiology of AMI. This case demonstrates the importance of recognising KS, advocates for restricting self-treatment practices, and highlights the need for preventive counselling regarding its potential consequences.